Optimizing gefitinib nanoliposomes by Box-Behnken design and coating with chitosan: A sequential approach for enhanced drug delivery - Seema Rohilla; Rajendra Awasthi; Ankur Rohilla; Sachin Kumar Singh; Dinesh Kumar Chellappan; Kamal Dua; Harish Dureja (International Association of Physical Chemists (IAPC), 2024)
This study aimed to improve the stability and prolonged gefitinib release from the nanoliposomes. Nanoliposomes were prepared by reverse-phase evaporation and optimized using Box-Behnken design to investigate the influence of sonication time (X1), tween 80 / soya phosphatidylcholine ratio (X2), and cholesterol / soya phosphatidylcholine ratio (X3) on nanoliposomes. Optimized nanoliposomes were quasi-spherical shaped, with a mean dimension of 93.2 nm and an encapsulation efficiency of 87.56±0.17 %. Surface decoration of the optimized batch was done using different concentrations of chitosan. The optimal chitosan concentration required to adorn the surface of nanoliposomes was 0.01 %. In comparison to unadorned nanoliposomes (82.16±0.65 %), adorned nanoliposomes (78.04±0.35 %) released the drug consistently over 24 h via Fickian diffusion. The IC50 values for surface-adorned nanoliposomes in A549 and H1299 cells were 6.53±0.75 and 4.73±0.46 µM, respectively. Cytotoxicity of the surface-decorated nanoliposomes may be due to their higher zeta potential and prolonged drug release. At 4°C, adorned and unadorned nanoliposomes are most stable. In conclusion, the developed nanoliposomes may offer a new path for melanoma clinics.